An investigation into the unacceptably high failure rate of boosters to determine the cause(s) of failure and then to implement the necessary corrective actions to improve the reliability - Nolte, Schalk Willem (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Ing.) -- University of Stellenbosch, 1986.